2015
DOI: 10.1111/echo.13135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Accuracy of Novel Automated Mitral Valve Quantification: Three‐Dimensional Transesophageal Echocardiographic Study

Abstract: The novel automated software package reduced time for quantification of MV with similar accuracy compared to the manual method. Automated quantification is useful and may be a key to widespread adoption of three-dimensional quantification in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…As previously reported by Kagiyama et al, MVN has been shown to have good inter‐observer agreement with automated and manual measurements as well as a reduction in time spent for analysis. We also believe that there is more consistency in selecting annular and commissural points using automated quantification.…”
Section: Discussionsupporting
confidence: 78%
“…As previously reported by Kagiyama et al, MVN has been shown to have good inter‐observer agreement with automated and manual measurements as well as a reduction in time spent for analysis. We also believe that there is more consistency in selecting annular and commissural points using automated quantification.…”
Section: Discussionsupporting
confidence: 78%
“…The MR grade was evaluated by measuring the color Doppler jet area or using the Doppler‐derived volumetric method or proximal isovelocity surface area method, according to previously published guidelines . A 3D‐TEE analysis was performed off‐line using the commercially available semiautomated software package Mitral Valve Navigation (Philips Medical Systems, Andover, MA), for which the accuracy and reproducibility of 3D quantification has been previously reported . The anterior mitral leaflet (AML) and PML angles were defined as the angles between the annular line and the line that joins the anterior/posterior annulus and coaptation point, respectively .…”
Section: Methodsmentioning
confidence: 99%
“…For intraoperative TEE assessment of residual MR, maximum regurgitant jet area (MRA) was used because quantification of residual MR, which is mostly less than mild, is difficult with the proximal isovelocity surface area method. In addition, 3D‐TEE analysis was performed off‐line using the commercially available semiautomated software package, MVN (Philips Medical Systems, Best, The Netherlands), whose accuracy and reproducibility of 3D quantification have been reported . Briefly, the diameters of the mitral annulus were measured between A2 and P2 (anteroposterior annular diameter) and between the anterolateral commissure and posteromedial commissure (commissure‐to‐commissure annular diameter).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 3D-TEE analysis was performed off-line using the commercially available semiautomated software package, MVN (Philips Medical Systems, Best, The Netherlands), whose accuracy and reproducibility of 3D quantification have been reported. 15 Briefly, the diameters of the mitral annulus were measured between A2 and P2 (anteroposterior annular diameter) and between the anterolateral commissure and posteromedial commissure (commissure-to-commissure annular diameter). Length and area of the AML (AML length, AML area) were also measured.…”
Section: Echocardiographymentioning
confidence: 99%